Immunopathological characterization of cryptoglandular anal fistula: a pilot study investigating its pathogenesis. (December 2016) - Ratto, C.; Litta, F.; Lucchetti, D.; Parello, A.; Boninsegna, A.; Arena, V.; Donisi, L.; Calapà, F.; Sgambato, A.
Abstract: Aim: The pathogenesis of cryptoglandular anal fistula (AF) is still under debate. Tissue inflammation could play a primary role. The pathological process of epithelial mesenchymal transition (EMT) might be involved but has never been investigated. Method: In a prospective pilot study, 12 patients with an AF had a fistulectomy. The excised track was divided into proximal (intrasphincteric) and distal (extrasphincteric) parts which were subjected to standard histopathological examination. The cytokines IL‐8 and IL‐1beta were analysed as markers of inflammation, while EMT was evaluated by expression of TGF‐beta, Vimentin, Zeb‐1, Snail and E‐cadherin. The mRNA and protein expression of these molecules was investigated by real‐time PCR (RT‐PCR), Western blot analysis and immunohistochemistry and was compared with that of the normal adjacent tissue. Results: Chronic inflammation and granulation tissue and a stratified epithelium were evident on standard histopathological examination. The cytokine IL‐8 was more expressed in the proximal than the distal part of the track (fold increase 4.34 vs 3.60), while the reverse was found for IL‐1beta (fold increase 1.33 vs 2.01); both were more intensely expressed compared with the normal anal mucosa. EMT was demonstrated, in both proximal and distal parts of the track, with an increase of TGF‐beta, Vimentin, Zeb‐1 and Snail and a mean decrease of E‐cadherin. Western blot analysis and immunohistochemistry confirmed the protein expression. Conclusion: The study suggests that chronic inflammation is present in cryptoglandular fistulas. The inflammatory pattern might be different in the proximal than in the distal part of the fistula track. The cytokines IL‐1beta and IL‐8 could play a possible role in fistula formation. The study demonstrates for the first time the potential importance of EMT in the pathogenesis of cryptoglandular AF.